If not now, why are you waiting?. Issue 2 (6th February 2018) - Butman, Samuel M.
Key Points: There is some surrogate outcome data supporting deferring PCI in STEMI No hard data to support deferring PCI in STEMI No hard data to refute deferring PCI in STEMI Current national quality measures do not offer a method to adequately document appropriateness of deferring PCI